2013
DOI: 10.2147/ijn.s42511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoencapsulation and PEGylation on biodistribution of indocyanine green in healthy mice: quantitative fluorescence imaging and analysis of organs

Abstract: Near-infrared nanoconstructs present a potentially effective platform for site-specific and deep tissue optical imaging and phototherapy. We have engineered a polymeric nanocapsule composed of polyallylamine hydrochloride (PAH) chains cross-linked with sodium phosphate and doped with indocyanine green (ICG) toward such endeavors. The ICG-doped nanocapsules were coated covalently with polyethylene glycol (5000 daltons) through reductive amination. We administrated the constructs by tail vein injection to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…At 10 h, the majority of the signal in the liver disappeared possibly due to recirculation and clearance. Similar clearance patterns have been reported by other groups as well [18, 19]. Bahmani et al, recently reported that after i.v.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…At 10 h, the majority of the signal in the liver disappeared possibly due to recirculation and clearance. Similar clearance patterns have been reported by other groups as well [18, 19]. Bahmani et al, recently reported that after i.v.…”
Section: Resultssupporting
confidence: 86%
“…Bahmani et al, recently reported that after i.v. injection of free ICG in healthy mice, the signal was detectable in the liver as early as 3 minutes post-injection, reaching a peak level between 5 and 10 min, indicative of a rapid hepatic clearance from the systemic circulation, while the fluorescence signal in the liver was found to increase up to 60 min time point after NP administration [18]. Zheng et al, underlined that the relatively short circulation time of the free ICG in vivo could be attributed to fluorescence quenching of free ICG in physiological environments [19].…”
Section: Resultsmentioning
confidence: 99%
“…In mice receiving ICG-loaded NP, the fluorescence signal appeared in the gastrointestinal tract, following the typical distribution of free ICG. 33 Therefore, we chose DiR as a fluorescence label of particles for in vivo imaging. We compared NPpT and NPpT-CA to evaluate the effect of surface modification on tumor accumulation of the particles, because they showed consistently smaller particle sizes than NL counterparts (Table 1) and the size difference – another significant factor that can affect biodistribution – was much smaller (177.0 nm vs. 179.5 nm) than that of NLpT and NLpT-CA (411.3 nm vs. 270.3 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of ICG enabled optical imaging, which has numerous advantages such as high sensitivity and spatial resolution, real-time high frame rate imaging, relatively low cost, portability, and lack of ionizing radiation exposure20. ICG fluoresces in the near infrared wavelengths, where there is negligible autofluorescence as well as limited scatter and absorption in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Free ICG has a short plasma half-life (~2–4 minutes)1819. Encapsulation increases circulation time and delays maximal hepatic accumulation (>1 hour)20. Encapsulation can also increase in vivo stability, and signal intensity21.…”
mentioning
confidence: 99%